2022
DOI: 10.21037/atm-22-2108
|View full text |Cite
|
Sign up to set email alerts
|

Candesartan induces tumor vascular normalization to improve the efficacy of radiotherapy in the therapeutic window

Abstract: Background: This study sought to examine whether candesartan induces tumor vascular normalization in a narrow therapeutic window to increase perfusion and oxygen content, and thus enhance the effect of radiotherapy (RT). Methods: Candesartan was administered to tumor-bearing mice to induce the normalization of tumor vessels, and the time window for normalization was determined. Then, tumor vascular density, perfusion, pericyte coverage, hypoxia of tumor-bearing mice was detected at 3, 6, 9, 12 days, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Additionally, HIF-1 regulates the expression of several other angiogenic factors, including placental growth factor, platelet-derived growth factor β (PDGF-β), and angiopoietin-1 and -2 (Ang-1 and Ang-2) [ 57 ]. For example, the angiotensin II receptor antagonist candesartan modulates tumor vascular normalization and improves the sensitivity of radiotherapy during the therapeutic window [ 60 ].…”
Section: Strategies To Regulate Vascular Normalizationmentioning
confidence: 99%
“…Additionally, HIF-1 regulates the expression of several other angiogenic factors, including placental growth factor, platelet-derived growth factor β (PDGF-β), and angiopoietin-1 and -2 (Ang-1 and Ang-2) [ 57 ]. For example, the angiotensin II receptor antagonist candesartan modulates tumor vascular normalization and improves the sensitivity of radiotherapy during the therapeutic window [ 60 ].…”
Section: Strategies To Regulate Vascular Normalizationmentioning
confidence: 99%
“…Vascular normalization therapy can inhibit the leakage of blood components, increase the drug concentration of tumor cells, and reduce cancer metastasis. [ 121 ]…”
Section: Tme and Tme‐related Sdtmentioning
confidence: 99%
“…Vascular normalization therapy can inhibit the leakage of blood components, increase the drug concentration of tumor cells, and reduce cancer metastasis. [121] Vascular normalization is beneficial for increasing the intratumor perfusion of nanodrugs by changing angiogenic factors to reshape the tumor's internal vascular system. However, this will increase the coverage of vascular pericytes and reduce the penetration ability of large nanoparticles.…”
Section: Abnormal Vascular System In the Tme And Sdt Combined With Va...mentioning
confidence: 99%
“…There are two main classes of drugs on the market that target RAAS to decrease blood pressure, either by directly competing with Angt II binding to AT1R (AT1R blockers: ARBs) or by inhibiting the angiotensin-converting enzyme (ACE) to prevent the production of Angt II. ARBs and angiotensin-converting enzyme inhibitors (ACE-Is) are gaining more attention for their potential to create TVN as a way to treat cancer [ 111 ]. In some retrospective studies, researchers found that cancer patients that were using previously prescribed ARB or ACE-I medication while receiving standard cancer treatments including chemotherapy, radiotherapy, or ICIs had better PFS and OS across various cancer types [ 112 , 113 ].…”
Section: Anti-cancer Treatments That Engender Tumor Vascular Normaliz...mentioning
confidence: 99%